Construction Supplier Selection Criteria: A Systematic Literature Review - Rigel Pawallo; Oei Fuk Jin (Jurnal Syntax Transformation, 2025)
This research proposes a new model for further research on how to choose criteria in supplier selection for construction sector, through a literature review and analysis of the advantages and disadvantages of previously used methods. The methods used to select criteria in construction supplier selection were extracted from various scopus databases. The weaknesses and advantages of these methods were then analyzed. Based on these findings, several opportunities for improvement are proposed for further research. Finally, criteria methods for the selection of suppliers are proposed using statistical Multi-Criteria Decision Making (MCDM) methods. Direction and guidance for subsequent research to select the criteria used in supplier selection, based on the advantages and disadvantages of the decision methods used. Limitations of this study are that it is focused on the methods of criteria design in the supplier selection. This study can provide a research direction on the design of criteria for supplier selection. This study provides ongoing guidance and avenues for further research. Use method / value for working out the developmental strategy for criteria selection are provided by statistical MCDM methods in the construction supplier selection.